The ideal of ’kalokagathia’ in Xenophon: an analysis of excesses - Sousa, Luana Neres de (Romanitas - Revista de Estudos Grecolatinos, 2013)
Xenophon, an Athenian polygraph who lived in the fifth century BC, produced a dialogue entitled Symposium which has as a conducting wire the actions of the virtuous men, i.e. the kaloikagathoi. Our goal is to identify what consisted as kalokagathia for Xenophon from the analysis of two of Symposium’s characters that constitute excess paradigms: Nikeratus and Critobulus.